Applications of LiNbO3 Nested Waveguide and Design of AlGaAs Nested Waveguide for Terahertz Difference Frequency Generation - Zenner, Chris (My University, 2011)
Nonlinear optics is the consequence of the nonlinear dependence of the polarization of a material on the incident electric field. Typically, to detect the nonlinear optical process the incident light must be relatively intense (~108 V/m) compared to the atomic fields. Because of this process, it is possible to develop light sources in frequency regimes where conventional methods no longer apply. In this project, the frequency of interest is ~1 - 3 THz. There is a high amount of research in the terahertz regime (0.3 - 3 THz) because of the possible applications in military and national security. As a result, there is a high demand for room-temperature, compact, high power conversion efficiency, narrow-linewidth, continuous wave (CW) sources. One possible solution is multilayer nested waveguides. It has been shown that intense light sources can cause nonlinear effects in bulk material, but to significantly improve the optical power of the THz source, multilayer waveguide structures offer much higher optical confinement, single mode operation, improved overlap of pumps and THz, and tuning ability. To model the IR and THz mode propagation in the multilayer, single mode waveguide, a beam propagation method (RSoft's BeamPROP) was used to calculate the effective index. The phase matching criteria discussed later in the paper was used to determine the frequency of the THz. The peak THz power was calculated by taking the overlap integral of the IR pump mode and THz mode. Because the model simulation worked accurately for the LiNbO3 nested waveguide, a modified version was used for the AlGaAs nested waveguide. Unfortunately, the current AlGaAs nested waveguide model did not produce the THz in the frequency range we calculated, and device limitations prevent the possibility of exploring higher frequency. The reason for the miscalculation could be from inaccurate index of refraction data for AlxGa1-xAs, high absorption peaks at the THz frequency, and/or an incorrect nonlinear polarization coefficient. Although the THz source did not produce measurable power at the scanned frequency range, it is still possible the device will produce THz at a higher frequency than current devices will allow. Therefore, in future research, it should be desirable to scan the upper frequency region above 4 THz.